Do different characteristics of two emasculators make a difference in equine castration?. (1st August 2017) - Comino, F.; Giusto, G.; Caramello, V.; Gandini, M.
Summary: Background: The Serra and Reimer emasculators are frequently used in equine orchiectomy. They differ in jaw profile and the mechanism by which they achieve haemostasis. Objectives: To investigate whether the haemostatic capacities of the Reimer and Serra emasculators in open and closed castration differ, to compare the haemostatic capacities of each emasculator in both open and closed castration, and to assess whether the tensile strength of the parietal tunic in closed castration differs according to whether a Reimer or Serra emasculator is used. Study design: Ex vivo randomised study. Methods: Eighty equine cadaver testes were randomly assigned to two groups for, respectively, open and closed castration. Each group was divided into two subgroups for castration with a Serra or Reimer castrator, respectively. Testicular artery leaking pressure was measured by dye injection. In closed castration, the tensile strength of the parietal tunic was measured with a tensiometer. Results: In open castration, the Reimer emasculator resisted significantly higher pressure (median: 706.1 mmHg; interquartile range [IQR]: 597.6–735.5 mmHg) than the Serra emasculator (median: 349.4 mmHg; IQR: 261.1–468.9 mmHg) (P<0.001), whereas no difference was found in closed castration (Serra emasculator, median: 382.5 mmHg [IQR: 294.2–568.2 mmHg]; Reimer emasculator, median: 419.2 mmHg [IQR: 294.2–616.0 mmHg]). The Reimer emasculator resisted significantly higher pressure in the open (median: 706.1 mmHg; IQR: 597.6–735.5 mmHg) compared with the closed (median: 419.2 mmHg; IQR: 294.2–616.0 mmHg) technique (P = 0.03). Parietal tunic tensile strength did not differ significantly by emasculator (mean ± s.d.: Serra, 12.65 ± 7.35; Reimer, 17.55 ± 11.76). Main limitations: Limitations are inherent to the ex vivo study design. Post‐surgery implications were investigated only in the short term and no account was taken of tissue inflammation and oedema, which may influence the integrity of the tissue. Conclusions: These results suggest it may be preferable to use a Reimer emasculator in open castration. In this ex vivo model of closed castration, no differences between the emasculators were observed.